Analisis terhadap Efektivitas Integrasi Media Digital dan Pembelajaran Berbasis Isu Mutakhir untuk Peningkatan Literasi Kewarganegaraan pada Era Masyarakat 5.0 - Asep Anggi Buldani; Jamaludin Jamaludin; Sunarto Amus; Taufiq Eka Riandhana; Dinie Anggraeni Dewi (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2026)
The Society 5.0 era has given rise to new citizenship challenges in the digital space, such as hoaxes, polarization of public opinion, hate speech, and low civic literacy. Civic education needs to transform from a theoretical approach to contextual, critical, and digital-based learning. This study aims to examine the effectiveness of issue-based civic education learning integrated with digital media in improving students' civic literacy in the era of Society 5.0. This approach places contemporary socio-political issues as the learning context that allows students to analyze real cases, test citizenship concepts reflectively, and formulate responsible civic attitudes and actions. The use of digital media strengthens this process by providing actual information sources, collaborative discussion spaces, and interactive media that encourage critical thinking and information literacy skills. The results of the study show that the integration of current issues and digital media has the potential to improve students' civic literacy, especially in terms of understanding citizenship issues, critical analysis skills, and awareness and responsibility in socio-political participation. Thus, this learning model is relevant to the character of Society 5.0 as a pedagogical innovation to strengthen civic competencies that are adaptive to the dynamics of digital society.